Social Studies: Level One Identity. Teacher's Guide and Resource Book=Araling Panlipunan: Unang Antas--Pagkakakilanlan. Ang Patnubay Ng Guro At Hanguang Aklat. - Berkeley Unified School District, CA. Asian American Bilingual Center; Berkeley Unified School District, CA. Asian American Bilingual Center; California State Univ., Los Angeles. National Dissemination and Assessment Center ([S.l.] : Distributed by ERIC Clearinghouse, 1980)
This Pilipino teacher's guide is part of Berkeley, California Unified School District Asian American Bilingual Center's effort to foster the total growth of the child. To facilitate that growth, the Center has selected an interdisciplinary approach to curriculum development. Social studies themes and concepts provide the framework within which all the subject areas, including mathematics, reading and language arts, fine arts, and science, are organized. The four social studies themes are child, family, community, and natural environment. The themes reappear and expand through the curriculum from one text to the next and correlate to the concepts of identity, needs, and interaction. Level One is designed for children in grades one and two. Each level develops one or more aspects of a theme as the child moves from simple to complex ideas and from understanding of self to understanding of society. Unit 1 of the document, entitled "Self-Worth," develops concepts concerning how people identify themselves with different kinds of information, how people are similar or different, how people change and grow, and the fact that people have a history. Unit 2, "Groups," develops the idea that while most people are members of families and family members share characteristics, different families have different lifestyles. The unit also explores how people can be members of different groups within a community. The document includes an introduction, notes to the teacher, and a resource guide. (SG)
Sponsoring Agency: Department of Education, Washington, DC.
ERIC Note: For related documents in the series, see SO 022 126-135.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Concept Formation; Curriculum Development; Family (Sociological Unit); Filipino Americans; Grade 1.; Grade 2.; Group Dynamics; Individual Development; Interdisciplinary Approach; Primary Education; Self Concept; Self Esteem; Tagalog; Teaching Guides; Thematic Approach; Guides, Classroom -- Teacher; Multilingual/Bilingual Materials